Plasma cholinesterase assay among Malaysian vector control operators occupationally exposed to insecticides - Rostam, Muhamad Ashraf; Hassan, Zuridah (Saudi German Hospitals (SGH) Group, 2011)
Increase in insecticide space spraying (fogging) activities in Selangor, Malaysia for management of dengue outbreaks submits vector control operators towards occupational low-level exposure towards hazardous organophosphate and pyrethroid compounds. Hence, this study was aimed to determine insecticide poisoning among these workers occupationally exposed to insecticides. Plasma cholinesterase level was assayed on 106 vector control operators (subject group) and 74 blood donor samples (control group) to identify insecticide poisoning. Information regarding the workers recent exposure, type of insecticides used and compliance to personal protective equipment was obtained through questionnaire. Statistical analysis was then applied to determine differences in cholinesterase mean level between the subject and control group. Comparison of mean cholinesterase level between the subjects (7879.70 ±227.94 IU/L) and control group (7067.86 ±1609.71 IU/L) showed significantly higher (p<0.05) mean cholinesterase level in the subject group. The study indicated absence of inhibition of cholinesterase level among subject group compared to the control group thus reflects free from organophosphate poisoning in the vector control operators. Majority of the vector control operators were Malays. Strict implementation of personal protective equipment use proved to prevent pesticide poisoning among these workers. These mean cholinesterase levels for both different cohorts is therefore recommended to be used as reference and need to be updated from time to time. However, it is better if each individual cholinesterase level is made available as compared to mean population value